Pemodelan Tata Ruang Pekarangan Rumah Tinggal Suku Madura Berbasis Tanaman Edible Lokal (Universitas Muhammadiyah Palembang, 2023)
Indonesia has very rich natural and cultural resources. One of them is the uniqueness of one of the islands in East Java, namely Madura. Madura has a different climate from most of East Java, so that allows for different natural resources. Conservation is one thing that can be done to protect biodiversity. Utilization of edible plants or plants that can be eaten is one way. There needs to be a modeling of the Madurese yard based on local edible plants. The method used in this research is qualitative with a phenomenological approach, namely understanding the phenomenon experienced by the research subject as a whole, and describing it. Several plants that have been identified as edible are moringa leaves, Chinese petai, katu, pumpkin, banana cobs and pumpkin leaves which are commonly consumed as daily food. While the people of Madura, who are known for their tradition of drinking herbal medicine, use several plants such as tamarind to mix their herbal medicine. So far, the use of yards in the area of Madura, Bangkalan in particular has grown organically. The results of the yard modeling proposed by the study are the utilization of the back of the long-crop arrangement for planting food crops, this is because only the back can be used as a family yard and use plant as a border.